The molecular evolution of the most dangerous emerging virus infections - Popov, N; Kolotova, T (Annals of Mechnikov’s Institute, 2020)
In this paper we reviewed what is known about the emerging viruses, the hosts that they originate in, and the molecular events that drive their emergence. When a pathogen crosses over from animals to humans, or an existing human disease suddenly increases in incidence, the infectious disease is said to be ‘emerging’. Most of the emerging pathogens originate from nonhuman animal species which has been termed natural reservoirs. The number of emerging infectious diseases has increased over the last few decades, driven by both anthropogenic and environmental factors such as population growth, urbanization, global travel and trade, intensification of livestock production. Now it has been believed that the emergence process may include four steps. On the first step the exposure of the humans to a novel virus occures. On the second step the subset of the viruses overcome the cross-species barrier. Host shifts have resulted in multiple human pandemics, such as HIV from chimps the H1N1, ‘‘spanish flu’’ from birds, SARS-CoV and virus Ebola from bats. Then some viruses enables to transmit from one human to another. And on the last step the viruses that are sufficiently transmissible between humans cause outbreaks and become endemic in human populations without the requirement of a natural reservoir. This review aims to discuss the molecular mechanisms that govern virus cross-species transmission and following stage, using the emergence of HIV, SARS-CoV, virus Ebola and influenza virus A as the models.Populations of many viruses harbour abundant genetic variability due to a combination of high mutation, recombination or reassortation rates and large population sizes. Mutations and recombinations has been associated with the increases in virulence, the evasion of host immunity and the evolution of resistance to antivirals. Genetic alterations in one species may results in the acquisition of variations that allow them to overcome cross species barriers and infect new hosts. Really, many recently emerged human diseases are caused by viruses that display active recombination or reassortment. The continual shuffling of genes of influenza A represents a example of the key role of reassortment for the new virus emergence. Available data demonstrate the possible origin of SARS-CoV from recombination of different bat SL-CoVs viruses strains. However in other cases the emergence of a specific virus cannot be directly attributed to its ability to recombine. For example, although SIV recombines at a high rate in natural reservoirs, there is no evidence that recombination assisted the cross-species transfer of the virus from the chimpanzee into humans. But mutagenesis and recombination actively shape the further molecular history of HIV in humans. Also it is not proved that recombination precede the cross-species jump of the Ebola virus. In summary, the available data suggest that although recombination, reassortment and mutagenesis is sometimes directly involved to the process of cross-species transmission, it is not a necessary precursor to successful viral emergence. Further investigations are required to reveal the role of genetic change in the history of virus emergence. We believethat comprehensive description of molecular evolution of new viruses has led to a better understanding of the causes and predictability of infection emergence.